SELECCIÓN DE PERSONAL DE LA HACIENDA ERIKITA - Astudillo Naranjo, Laura Marivel (2019)
Large and medium-sized companies apply strategies for the personnel selection process for which they use selection models. The selection of personnel consists in choosing the candidate whether he is outside or inside the company to perform the requested position. An adequate selection must allow knowing the aspirants and that they also know the company. The selection is a process by which the characteristics and aptitudes of the candidates are evaluated and it is determined which meets the requirements so that this can be accepted. Start with the recruitment, after this comes the interview, this serves to complete the information of the applicant with a series of questions such as family responsibilities, salary that aspires, expected to find in the work, what needs, what work would you like to perform , what are your likes and likings